What works to promote walking at the population level? A systematic review. Issue 12 (31st May 2018) - Foster, Charlie; Kelly, Paul; Reid, Hamish A B; Roberts, Nia; Murtagh, Elaine M; Humphreys, David K; Panter, Jenna; Milton, Karen
Abstract : Objective: Interventions to promote walking have focused on individual or group-based approaches, often via the randomised controlled trial design. Walking can also be promoted using population health approaches. We systematically reviewed the effectiveness of population approaches to promote walking among individuals and populations. Design: A systematic review. Data sources: 10 electronic databases searched from January 1990 to March 2017. Eligibility criteria: Eligibility criteria include pre-experimental and postexperimental studies of the effects of population interventions to change walking, and the effects must have been compared with a 'no intervention', or comparison group/area/population, or variation in exposure; duration of ≥12 months of follow up; participants in free-living populations; and English-language articles. Results: 12 studies were identified from mostly urban high-income countries (one focusing on using tax, incentivising the loss of parking spaces; and one using policy only, permitting off-leash dogs in city parks). Five studies used mass media with either environment (n=2) or community (n=3) approaches. Four studies used environmental changes that were combined with policies. One study had scaled up school-based approaches to promote safe routes to schools. We found mass media, community initiatives and environmental change approaches increased walking (range from 9 to 75 min/week).